2022
DOI: 10.1371/journal.pone.0262612
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in suppression of osteoclast supportive activity by transforming growth factor-β1 via the ubiquitin-proteasome system

Abstract: Orthodontic treatment requires the regulation of bone remodeling in both compression and tension sides. Transforming growth factor-β1 (TGF-β1) is an important coupling factor for bone remodeling. However, the mechanism underlying the TGF-β1-mediated regulation of the osteoclast-supporting activity of osteoblasts and stromal cells remain unclear. The current study investigated the effect of TGF-β1 on receptor activator of nuclear factor kappa-B ligand (RANKL) expression in stromal cells induced by 1α,25(OH)2D3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Similar findings were observed in relevant studies [13,25] . However, TGF-β1 has also inhibited RANKL and promoted OPG expression in the case of 1α,25(OH)2-vitamin D3 stimulation, which reduced osteoclast production in a co-culture environment [15,[26][27] . TGF-β1 was introduced in these studies to activate p-Smad3, the final results may have been interfered with owing to the presence of other TGF-β1-related signaling pathways in addition to the pathway that activates p-Smad3 [28] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Similar findings were observed in relevant studies [13,25] . However, TGF-β1 has also inhibited RANKL and promoted OPG expression in the case of 1α,25(OH)2-vitamin D3 stimulation, which reduced osteoclast production in a co-culture environment [15,[26][27] . TGF-β1 was introduced in these studies to activate p-Smad3, the final results may have been interfered with owing to the presence of other TGF-β1-related signaling pathways in addition to the pathway that activates p-Smad3 [28] .…”
Section: Discussionmentioning
confidence: 98%
“…However, different findings have been reported that TGF-β1 downregulated the RANKL stimulated by 1α,25(OH)2-vitamin D3 and Dex in ST2 cells and inhibited osteoclast differentiation. The inhibition of the RANKL was reversed by blocking Smad2/3 using A83-01 or siRNA [15] . Smad3 has differential regulatory effects on the osteogenic lineage from different origins and osteoblasts at different stages of differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the first phases of osteoblast development, TGF-1β increases the synthesis of extracellular bone matrix protein by osteoblasts, thus maintaining bone health [134]. Estrogen increases osteoblast proliferation and differentiation by increasing the synthesis of TGF-β1 in osteoblasts [135]. In addition, estrogen inhibits bone loss by encouraging osteoclast apoptosis through a TGF-dependent process [136].…”
Section: Transforming Growth Factor β (Tgf-β)mentioning
confidence: 99%
“…TGFβ1 inhibited RANKL expression and osteoclast-supporting activity of osteoblasts/stromal cells induced by D3 and Dex through RXRprotein degradation mediated by the ubiquitin-proteasome system. TGFβ1 exerts complex and biphasic effects on osteoclastogenesis [91]. TGFβ also increases osteoblast lineage RANKL expression, thereby fostering the recruitment of osteoclast precursors [92].…”
Section: Tgfβ and Bonementioning
confidence: 99%